1991
DOI: 10.1080/09583159109355207
|View full text |Cite
|
Sign up to set email alerts
|

Biology and development of some stored grain pests as affected byδ‐endotoxin andβ‐exotoxin ofBacillus thuringiensis

Abstract: Exposure of Plodia interpunctella and Sitotroga cerealella to sublethal concentrations of Dipel 2X® (Bacillus thuringiensis var.kurstaki-HD-1) with its spores and endotoxin crystals led to an increase in the sum of larval-pupal duration. A decrease in moth emergence, egg production and fertility was observed with increase of Dipel 2X concentration, while the longevity of the moths was not affected by treatment. Sublethal concentrations of β-exotoxin (ABG-6162 A) had no significant effect on the sum of larval-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…A previous study of Bt-susceptible and -resistant Indianmeal moth colonies indicated no differences in development time or larval weight, but a substantial increase in mortality was observed in Bt-resistant colonies reared on diet that did not contain Bt (Johnson & McGaughey, 1996). Another study reported an increase in development time in moths fed sublethal concentrations of Bt subspecies kurstaki HD-1, and increased concentrations resulted in decreased moth emergence and fertility (Salama et al, 1991). Also in the Indianmeal moth, resistance to another microbial insecticide, a granulosis virus, was associated with lower egg viability, longer development time, and increased adult weight (Boots & Begon, 1993).…”
Section: Introductionmentioning
confidence: 95%
“…A previous study of Bt-susceptible and -resistant Indianmeal moth colonies indicated no differences in development time or larval weight, but a substantial increase in mortality was observed in Bt-resistant colonies reared on diet that did not contain Bt (Johnson & McGaughey, 1996). Another study reported an increase in development time in moths fed sublethal concentrations of Bt subspecies kurstaki HD-1, and increased concentrations resulted in decreased moth emergence and fertility (Salama et al, 1991). Also in the Indianmeal moth, resistance to another microbial insecticide, a granulosis virus, was associated with lower egg viability, longer development time, and increased adult weight (Boots & Begon, 1993).…”
Section: Introductionmentioning
confidence: 95%